Ligninolytic Activity of Fungi Isolated from Empty Fruit Bunch of Oil Palm (Elaesis guineensis Jacq.) - N S Sepwin; Erman Munir; It Jamilah (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
Lignin is a natural polymer and plays an important role as a compound of plant cell wall constituent. A study about the degradation of lignin in the environment has been receiving considerable attention because the complex structure and difficult to be degraded compared to the degradation of others plant cell wall constituent. A study to determine the activity of the ligninolytic enzyme (lignin peroxidase, manganese peroxidase and laccase) of fungi isolated from oil palm empty fruit bunch. This study has been done with a screening of ligninolytic activity using potato dextrose agar supplemented with tannic acid (0,1%), showed that two out of five fungal isolates have ligninolytic activity. The highest activity of lignin peroxidase was produced by SN2 isolatesi.e. 9.677U ml-1, whereas the highest activity of manganese peroxidase and laccase was produced by SN3isolates i.e.1.942 U ml-1 and 1.846 U m-1 respectively.